Organization of regional development work - Dale, Reidar (Ratmalana, Sri Lanka : Sarvodaya Book Pub. Services, 1992)
Study of various integrated rural development programs in Sri Lanka.
Includes bibliographical references (p. [531]-541) and index.
Keywords: Regional planning -- Sri Lanka